2011
DOI: 10.1007/s00520-011-1275-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the supportive and palliative oncology literature: a focused analysis on randomized controlled trials

Abstract: We identified deficiencies in the quality of supportive and palliative oncology RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 37 publications
3
28
0
1
Order By: Relevance
“…[152][153][154] However, despite the methodological concerns described above, no such overview exists within the area of chronic wounds, an area of medicine in which most treatments are medical devices for which RCT data are not necessary for licensing and marketing.…”
Section: Service User and Provider Perspectives (Worktream 2)mentioning
confidence: 99%
“…[152][153][154] However, despite the methodological concerns described above, no such overview exists within the area of chronic wounds, an area of medicine in which most treatments are medical devices for which RCT data are not necessary for licensing and marketing.…”
Section: Service User and Provider Perspectives (Worktream 2)mentioning
confidence: 99%
“…8 A recent study that evaluated supportive and palliative oncology clinical trials published in 2004 and 2009 showed a full description of the required SSC parameters in only 23% of cases. 9 There is a paucity of studies examining SSC reporting in oncology, especially in therapeutic trials. Given the methodological and ethical implications of inadequate SSC reporting, we aimed to evaluate the quality of such reporting in recently published phase III trials.…”
mentioning
confidence: 99%
“…Industry, and to a lesser degree federal government sponsorship, may significantly influence the methodological quality of RCTs in oncology. 3,[6][7][8] Consider item 5 in the CONSORT checklist, which requires that the study describe the interventions for each group in sufficient detail to allow replication by other parties. What is not required is an account of why a specific intervention was chosen for a particular comparative group.…”
Section: Letter To the Editormentioning
confidence: 99%